Kesetaraan Gender Akuntan Akademisi Perempuan Pasca Pandemi: Tantangan atau Rintangan Keberlanjutan Karir? - Noviriani, Eliza; Fitriana, Annisa (Pusat Penelitian dan Pengabdian kepada Masyarakat Politeknik Negeri Balikpapan., 2024)
This research was sparked from the diversity of research results regarding gender equality in the accounting profession. Many studies have concluded that equality between women and men especially in the accounting profession. On the other hand, there are also many studies that find that gender discrimination against female accountants is still rife. Based on this fact, this research expands the study of gender equality within the scope of vocational education by combining quantitative studies through measuring the perceptions or beliefs of female academic accountants using the Career Pathways Survey (CPS) and qualitative methods using phenomenological approach. The results of a survey of 50 female and an empirical study of 5 of them resulted in findings that gender equality has not been fully realized. The “voice” of female is divided into two parts: women who feel gender equality and women who experience gender discrimination. The reality arises from the organizational environment but cannot be separated from internal influences. Female academic accountants feel that feminist stereotypes are indeed “decent” to limit their career development steps. On the other hand, female academic accountants in polytechnic circles who are classified as advanced state that there is no difference in treatment between women and men.